Internal impingement - the pathological cascade - Karelse, A.; de Beer, J. (Medicine and Science in Tennis, 2007)
Scapular dyskinesia due to repetitive overhead movements is among the common problems of the tennis playing shoulder. The resulting ante-tilting of the glenoid together with the anteroinferior laxity and posterior tightness of the capsule causes a shift of the center of rotation of the shoulder. Abduction-external rotation movements will induce a posterosuperior shift of the humeral head resulting in a posterior SLAP lesion, possibly progressing to an articular side rotator cuff tear which can evolve to a full thickness tear.